The pathways from a behavior change communication intervention to infant and young child feeding in Bangladesh are mediated and potentiated by maternal self-efficacy - Zongrone, Amanda; Menon, Purnima; Pelto, Gretel H.; Habicht, Jean-Pierre; Rasmussen, Kathleen M.; Constas, Mark A.; Vermeylen, Francoise; Adiba, Khaled; Saha, Kuntal K.; Stoltzfus, Rebecca J. (Oxford University Press, 2018)
In the context of a behaviour change intervention (BCI) in Bangladesh, we studied the role of maternal self-efficacy for complementary feeding (MSE-CF) for 2 complementary feeding (CF) behaviors with the use of a theoretically grounded empirical model of determinants to illustrate the potential roles of MSE-CF. MSE-CF was a significant mediator and potentiator for GLV but not for EGG. The divergent findings highlight the complex determinants of individual specific infant and young child feeding behaviors. The study shows the value of measuring behavioral determinants, such as MSE-CF, that affect a caregiver's capability to adopt intervention-targeted behaviors.